Sorption and desorption of Pb(II) to biochar as affected by oxidation and pH - Wang, Qian; Wang, Bing; Lee, Xinqing; Lehmann, Johannes; Gao, Bin (The Science of the total environment, 2018)
The use of biochar for the removal of heavy metals from water has environmental benefits. In order to elucidate the potential application of highly functionalized biochar for the removal of Pb(II) in aqueous solution, maple wood biochar was oxidized using hydrogen peroxide. The pH values of oxidized biochar ranged from 8.1 to 3.7, with one set being adjusted to a pH of 7 as a comparison. It was found that oxidizing the biochars increased their Pb(II) adsorption capacity if the pH remained below 6 (strong oxidation), but decreased their Pb(II) adsorption ability above pH6 (weak oxidation). After adjusting the pH of oxidized biochar to pH7, the Pb(II) adsorption capacity further increased two to sixfold for oxidized biochars originally at pH3.7–6. The adsorption characteristics of Pb(II) were well described by the Langmuir equation. Adsorption of Pb(II) was not fully reversible in water. Less than 6% of Pb(II) desorbed in water in two consecutive steps than was previously adsorbed, for biochars with a pH below 7, irrespective of oxidation. Recovery using an extraction with 0.1M NaNO3 increased from 0.7% to 32.7% of Pb(II) undesorbed by both preceding water extractions with increasing oxidation, for biochars with a pH below 7. Unextractable Pb(II) was lower at low oxidation but increased to 99.0% of initially adsorbed amounts at low pH, which indicated that the adsorption of Pb(II) on oxidized biochar is pH independent. [Display omitted] •Adsorption is largely affected by oxygen-containing surface functional groups and pH.•Oxidation increases the affinity of Pb(II) to biochar and decreases the desorption in water.•Pb(II) adsorption is not fully reversible using NaNO3 irrespective of oxidation.•Oxidized biochar has the potential for Pb(II) immobilization.